Contrasting rift and subduction-related plagiogranites in the Jinshajiang ophiolitic mélange, southwest China, and implications for the Paleo-Tethys - Zi, Jianwei; Cawood, P.; Fan, W.; Wang, Y.; Tohver, E. (American Geophysical Union, 2012)
The Jinshajiang ophiolitic mélange zone in southwest China represents a remnant of the eastern Paleo-Tethys Ocean. Field, geochronological and geochemical studies have identified two distinct suites of plagiogranites within the mélange, the Dongzhulin trondhjemite and Jiyidu tonalite, which represent rift and subduction settings, respectively, related to opening and closing of the ocean. SHRIMP U-Pb analysis on zircons extracted from the Dongzhulin trondhjemite yields a mean 206Pb/238U age of 347 ± 7 Ma. REE and isotopic characteristics suggest an origin from low pressure partial melting of an amphibolitic protolith. Highly variable Hf isotopic compositions for zircons from this body may indicate a heterogenous source involving both depleted mantle and enriched continental components. This, together with geologic relations, suggests formation near an embryonic spreading center in a continent-ocean transition setting. The Jiyidu tonalite has a U-Pb zircon age of 283 ± 3 Ma, and geochemical data indicates high Sr/Y, (La/Yb)N, Nb/Ta and low Y, and marked heavy REE depletion. These signatures suggest derivation from low degree partial melting of subducted slab at pressure high enough to stabilize garnet and rutile. A slab-melt origin is also supported by in situ Hf and O data for zircon that show isotopic compositions comparable with typical altered oceanic crust. Thus, the crystallization age of the Jiyidu high Sr/Y tonalite provides a constraint for the subduction of the Jinshajiang ocean floor. The rift-related Dongzhulin trondhjemite and subduction-related Jiyidu high-Sr/Y tonalite constrain the timing and setting of opening and closing of this segment of the Paleo-Tethys Ocean.